O princípio constitucional da fraternidade como fundamento para a concretização do direito ao desenvolvimento da juventude vulnerável no Brasil - Guimarães, Geane Monteiro (2024)
The research has as its central theme the constitutional principle of fraternity as the basis for realizing the right to development of vulnerable youth in Brazil. A considerable portion of Brazilian youth has been neglected, more specifically as a result of poverty and stigmatization due to structural racism. This research initially analyzes the evolution of constitutionalism until the formation of the fraternal State, seeking then to present the constitutional principle of fraternity as a foundation for the implementation of the Right to Development, analyzing the birthplace of fraternity, the Law to Development in the international order and both as presuppositions of Brazilian fraternal constitutionalism. Later on, the research starts to deal directly with youth issues. Thus, it presents, firstly, the young person as a subject of rights and obligations and their inclusion in Brazil's constitutions and infra-constitutional legislation. The study then evolves to demonstrate that poverty segregation and racism are factors that make youth vulnerable in Brazil, preventing their access to better levels of social well-being. In the end, some challenges that exist for promoting youth development in Brazil are also highlighted, including those linked to international policies, as well as some instruments that can assist internally in this development.